An intestinal Trojan horse for gene delivery. Issue 10 (14th March 2015) - Peng, Haisheng; Wang, Chao; Xu, Xiaoyang; Yu, Chenxu; Wang, Qun
<x xml:space="preserve">Abstract</x> A novel intestinal "Trojan horse" for potential gene therapy of intestinal disorders.